Automated model-based test case generation using UML activity diagram - Monim, Md Abdul (2018)
Software or application testing is a process of executing a program with the goal of finding defect to make better system. In software testing phase, writing test cases is one of the important activities. Manually writing test cases approach is lengthy of time period and need more effort to accomplish the process. On the other hand, automated test case generation technique is the way to solve this issue and Model-Based Test case generation approach would be the appropriate for this automation process. Usually, a model is required in Model-Based Testing approach to generate the test cases. This study aimed is to develop an automated tool that canbe able to generate test cases from UML activity diagram. This study has successfully developed the automated test case generating tool based on Model-Based Testing approach that could generate test cases automatically using UML activity diagram as an input. In addition, the proposed model and technique has explained detail in this thesis. Furthermore, an expert review based on Post Study System Usability Questionnaire (PSSUQ) method was also conducted to evaluate the tool and also verify the study requirement and objectives. A group of experienced software testing expert was involved in this evaluation phase. As result, the evaluation was satisfied all the objectives. Based on this study, some future recommendations have been proposed also for the extension of the developed tool’s quality and functionality to make a better tool.